Director training and financial disclosure: Asian insights - Qaiser Rafique, Yasser; Abdullah, Al Mamun; Rodrigs, Marcus (University of Finance and Management in Warsaw, 2017)
We provide evidence regarding the relationship between director training programs and improved financial reporting. Director Training Programs (DTP) help directors better understand the specific context in which a firm operates, including its operations and environment; awareness of business norms and values; standards of probity and accountability; and their fiduciary duties as an agent of investors. This study explores a recent requirement for director training and its effect on the quality of financial reporting for publicly listed companies in three eastern countries. This study examines the relationship between DTP and the quality of financial reporting of Australian, Malaysian and Pakistani publicly listed companies by using a sample of data from 2011 to 2013. We determined that Australian companies that incur additional DTP expenditures and have a flexible training schedule (Online DTP)improve their financial reporting quality and that a well established DTP positively affects financial reporting quality in Malaysia. In addition, the results indicate that firm size negatively affects financial reporting quality in the Asia Pacific and older companies (firm age) suffer from low-quality financial reporting. © 2017, University of Finance and Management in Warsaw. All rights reserved.